PEMANFAATAN LAHAN DAN PENGELOLAAN SUMBERDAYA HUTAN OLEH MASYARAKAT SEKITAR KAWASAN HUTAN LINDUNG GUNUNG SIRIMAU (STUDI KASUS DI DESA HUKURILA KOTA AMBON) - Mersiana Sahureka (JURNAL HUTAN PULAU-PULAU KECIL, 2016)
Socio-economic and cultural life of rural communities in an effort Hukurila land use and management of forest resources to meet the needs of life is a hereditary habits are not many greet the change . Research conducted in the village of Hukurila aims to : 1 ) determine the characteristics of rural communities Hukurila role in the management of natural resources , 2. Knowing the diversity of land use by communities Hukurila 3.Mengetahui stages of land management by communities Hukurila. The method used is survey analysis by doing a direct observation, selection and sampling locations is done with a specific purpose ( purposeful ) with 15 respondents coupled with key informants : Saniri country ( village government ) and related instransi , and NGO. The results showed the characteristics of the community in the utilization and management of forest resources based on age class , level of education , type of work and the amount of income . The pattern of land use by communities Hukurila can be divided into five (5 ) the yard , garden, Dusung agroforestry , forest , coast. While the stages of land management consists of Preparation , planting , maintenance , harvesting , marketing , post-harvest processing .